2007
DOI: 10.1164/rccm.200701-085oc
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Evaluate Safety and Efficacy of Mepolizumab in Patients with Moderate Persistent Asthma

Abstract: Mepolizumab treatment does not appear to add significant clinical benefit in patients with asthma with persistent symptoms despite inhaled corticosteroid therapy. Further studies are needed to investigate the effect of mepolizumab on exacerbation rates, using protocols specifically tailored to patients with asthma with persistent airway eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
418
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(447 citation statements)
references
References 39 publications
16
418
1
12
Order By: Relevance
“…IL-5 is a potent therapeutic target due to its causative relationship to eosinophilia. Therapies for asthma targeting IL-5 are currently being re-evaluated, and promising results have been obtained (47)(48)(49)(50). Therefore, innate IL-5-producing cells should be preferable candidates to study allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 is a potent therapeutic target due to its causative relationship to eosinophilia. Therapies for asthma targeting IL-5 are currently being re-evaluated, and promising results have been obtained (47)(48)(49)(50). Therefore, innate IL-5-producing cells should be preferable candidates to study allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested a key therapeutic target, but early clinical trials with anti-IL-5 monoclonal antibodies for atopic dermatitis, eosinophilic esophagitis, and asthma yielded mixed to negative results (Leckie et al, 2000;Oldhoff et al, 2005;Flood-Page et al, 2007). Although some of these findings may have reflected patient selection (Haldar et al, 2009;Bel et al, 2014;Ortega et al, 2014), these trials have not revealed a clear pathological role for eosinophils in allergic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response in asthma is orchestrated by CD4 T h 2 cells inducing eosinophil infiltration and mast cell activation, followed by tissue remodeling, mucus hypersecretion, and airway hyperresponsiveness (3). While it is clear that immune mechanisms play a significant role in the development and maintenance of asthma, the limited efficacy of immune therapies suggests the involvement of additional mechanisms and physiological systems in the disease process (4).…”
mentioning
confidence: 99%